2011
DOI: 10.1111/j.2044-8325.2010.02014.x
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment processes and gain spirals at work and at home: A 3-year cross-lagged panel study

Abstract: In this study, we combined the Job Demands‐Resources model and Conservation of Resources theory with work‐family enrichment (WFE) literature, using the Resource–Gain–Development perspective in particular, in order to (1) investigate the motivating and wellness‐promoting role of job and home resources in predicting enrichment in work and family leading to further positive outcomes, and (2) examine positive gain spirals between the study variables over time. More specifically, we investigated whether job resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(145 citation statements)
references
References 57 publications
6
135
1
3
Order By: Relevance
“…Over the years, work engagement research has shown that the construct is stable, permanent and long lasting (Hakanen, Peeters & Perhoniemi, 2011;Schaufeli, Bakker & Van Rhenen, 2009). However, several studies have indicated that job resources are positively related to work engagement over time and, furthermore, discovered that there exists a reciprocal causal relationship present, where job resources predict work engagement, which in turn predicts job resources over time (Mauno, Kinnunch, Mäkikangas & Feldt, 2010;Simbula, Guglielmi & Schaufeli, 2011;Xanthopoulou et al, 2009).…”
Section: Relationships Between Perceived Organisational Support For Smentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, work engagement research has shown that the construct is stable, permanent and long lasting (Hakanen, Peeters & Perhoniemi, 2011;Schaufeli, Bakker & Van Rhenen, 2009). However, several studies have indicated that job resources are positively related to work engagement over time and, furthermore, discovered that there exists a reciprocal causal relationship present, where job resources predict work engagement, which in turn predicts job resources over time (Mauno, Kinnunch, Mäkikangas & Feldt, 2010;Simbula, Guglielmi & Schaufeli, 2011;Xanthopoulou et al, 2009).…”
Section: Relationships Between Perceived Organisational Support For Smentioning
confidence: 99%
“…Firstly, a longitudinal approach was undertaken to explore causal relationships between the constructs. However, it has been recorded that both strengths use and work engagement are stable phenomena (Hakanen et al, 2011;Mauno et al, 2007;Schaufeli et al, 2009;Van Woerkom et al, 2015) and therefore utilising research designs with a shorter time frame, such as weekly diaries, could better explain variations and differences in the levels of the constructs (Bakker & Bal, 2010;Fritz & Sonnentag, 2007).…”
Section: Limitations and Recommendationsmentioning
confidence: 99%
“…En cuanto a las consecuencias del ETF, investigaciones previas han demostrado que el compromiso (Hakanen, Peeters, & Perhoniemi, 2011); la satisfacción (Masuda, McNall, Allen, & Nicklin, 2012;McNall et al, 2010), y el rendimiento (Odle-Dusseau, Britt, & GreeneShortridge, 2012), suelen ser el resultado del enriquecimiento en uno u otro sentido.…”
Section: La Red Nomológica Del Enriquecimientounclassified
“…They found out that both development I-deals (employees negotiate their demand beyond work boundaries) and flexibility I-deals (employees negotiate their working times and schedules beyond required and expected work time policy and norms) are the antecedents of the WFE in Chinese context. Another study conducted by Hakanen et al (2011) further proved the boundaryless domains during the WFE process. They found that the WFE process is reciprocal association due to gain spirals.…”
Section: Life Enrichment For Workersmentioning
confidence: 99%